Comparative value of current literature of England and America - Hall, Susie (My University, 1893)
Introduction: In the past we have looked to Europe and especially to England for our best literary productions but we believe the time is soon coming when we need look no farther than the boundaries of our own country for the most talented writers of the world. Although America’s literary career comprises over a century little of value was written until during the last fifty years when the standard has been steadily advancing. A comparison of the leading current writers of the two countries may surprise some who have not made a study of the subject by showing that while America has been progressing so rapidly in other directions she has not neglected her literature.
Citation: Hall, Susie. Comparative value of current literature of England and America. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Literary productions; Literature; America; Theses; Manuscripts (documents)